2016
DOI: 10.1136/thoraxjnl-2016-208494
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of vitamin E isoforms on asthma and allergic airway disease

Abstract: Prospective epidemiological studies, observational cross-sectional studies and some randomised prevention trials have demonstrated inconsistent findings of the impact of vitamin E on asthma risk. The goals of this study were to explore whether this differing association of vitamin E on asthma risk is due to an interaction of vitamin E isoforms. To address this question, in a population-based asthma incidence study we assessed the interaction between the plasma concentrations of vitamin E isoforms α-tocopherol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 19 publications
4
18
1
5
Order By: Relevance
“…Vitamin E has antioxidant properties and has been inconsistently linked to reduced risk of asthma. 47 In contrast and consistent with our findings, the g-tocopherol form, which has increased in Western diets over recent decades, 48 has been associated with increased asthma risk or severity, [48][49][50] although some analyses find anti-inflammatory effects. 51 The systems effects of dietary vitamin E intake on the microbiome and metabolome are worthy of further investigation and might have relevance to asthma.…”
Section: Discussionsupporting
confidence: 86%
“…Vitamin E has antioxidant properties and has been inconsistently linked to reduced risk of asthma. 47 In contrast and consistent with our findings, the g-tocopherol form, which has increased in Western diets over recent decades, 48 has been associated with increased asthma risk or severity, [48][49][50] although some analyses find anti-inflammatory effects. 51 The systems effects of dietary vitamin E intake on the microbiome and metabolome are worthy of further investigation and might have relevance to asthma.…”
Section: Discussionsupporting
confidence: 86%
“…Endothelial cells pretreated with α -tocopherol are less prone to let the lymphocytes and eosinophils migrate, while the opposite is true when pretreated with γ -tocopherol, this is due to the fact that the first strategy decreases VCAM-1 expression, while the latter increases it [ 80 ]. This phenomenon was observed even in vivo, in a mouse model of allergic lung inflammation [ 80 , 81 ].…”
Section: Exogenous Antioxidants and Human Healthmentioning
confidence: 99%
“…On the other hand, Cook-Mills J et al reported that the risk of asthma is increased in low levels of α-tocopherol with high levels of γ-tocopherol. 51 Again, further study is necessary to clarify the relationships between α-tocopherol and γ-tocopherol in patients with established asthma.…”
Section: Discussionmentioning
confidence: 99%